2014
DOI: 10.1590/s1808-18512014130400474
|View full text |Cite
|
Sign up to set email alerts
|

Motor and histological findings in a model of sci: comparison between posterior and lateral clips

Abstract: Objective: To evaluate the locomotor and histological impact on the spinal cord comparing lateral and posterior clip placement. Method: Randomized experimental trial. Twenty female Wistar rats, weighing between 250 and 300 grams and aged 12-14 weeks were randomized in two groups according to the placement of the clip: lateral group (N=10) and posterior group (N=10). After exposing the thoracic segment of the spine (T8-T10), a laminectomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…We found that SCI induced by Merocel ® expansion resulted in better locomotor function and less severe histological changes, including hemorrhage, inflammatory cell recruitment, and spared white matter in the core region, compared to SCI induced by clip compression. 10) These results suggest that the Merocel ® model simulates incomplete SCI and may represent therapeutic decompressive laminectomy for discogenic incomplete SCI.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…We found that SCI induced by Merocel ® expansion resulted in better locomotor function and less severe histological changes, including hemorrhage, inflammatory cell recruitment, and spared white matter in the core region, compared to SCI induced by clip compression. 10) These results suggest that the Merocel ® model simulates incomplete SCI and may represent therapeutic decompressive laminectomy for discogenic incomplete SCI.…”
Section: Discussionmentioning
confidence: 70%
“…Therefore, previous animal studies used blunt trauma injury patterns such as contusion or compression in 62% of studies. 10 31) The severity of injury was complete in 52% and incomplete in 48% of studies. 31) Compression models are helpful to simulate compression and contusion, which are common in human SCIs, and to study the effects of therapy.…”
Section: Discussionmentioning
confidence: 99%